Exploring the Interconnection Between Islamic Culture and Tourism Development in Malaysia - Badawi, Ahmad (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2025)
This study examines the interplay between tourism and Islamic culture in Malaysia, highlighting how cultural heritage and religious practices influence the tourism landscape. Malaysia, as a predominantly Muslim country, provides a unique environment where Islamic values intersect with tourism, shaping visitor experiences. The research employs qualitative methods, including interviews with local stakeholders and analysis of tourism policies, to understand how Islamic culture is utilized to promote tourism. Findings reveal that Malaysia's rich Islamic heritage, including mosques, festivals, and culinary traditions, not only attract international tourists but also promote cultural awareness among locals. However, challenges arise in balancing the commercialization of cultural practices with the need for authenticity and respect for religious values. The study concludes that integrating Islamic culture into tourism development offers opportunities for sustainable tourism while preserving cultural identity. Recommendations for enhancing the synergy between Islamic culture and tourism practices in Malaysia are also discussed, encouraging local communities to engage in authentic cultural representations that resonate with tourists.